Architecture, Religion, and the Forms of Nature in Turn-of-the-Twentieth-Century Chicago - Ellis, Isaiah (Journal for the Study of Religion, Nature and Culture, 2021)
The commercial architectural style that emerged in Chicago in the late nineteenth-century United States constituted a material gathering point for that century’s masculinities, religious histories, and conceptions of nature. This was especially true in the case of Louis Henri Sullivan (1856–1924), an inmuential lgure in crafting the aesthetic of this ‘Chicago School’ of architectural practice. Drawing on transcendentalist literature and recent innovations in architectural design, Sullivan outlined an ‘organic’ theory of architecture made famous in his pithy expression: form follows function. His design and theorization of free-standing structures offered gendered forms as the constitutive vocabulary of American architecture, with those very forms—not just the skyscraper but the free-standing structure writ-large—governing the relation of nature and its spirit to the masculinized landscape of urban commercial expansion. In Sullivan’s work, the gendered body became the vehicle for natural laws, both material and divine.